2017
DOI: 10.3892/ol.2017.6152
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter research into the quality of life of patients with advanced oropharyngeal carcinoma with long-term survival associated with human papilloma virus

Abstract: The treatment of advanced-stage oropharyngeal squamous cell carcinoma may utilize various modes, including combining surgery with chemoradiotherapy (CTRT), or primary CTRT followed by rescue surgery. In previous literature it has been revealed how patients treated with combined modes report a low quality of life (QoL) and severe consequences following surgery, radiotherapy and chemotherapy, in the short and in the long-term. The decrease in the QoL of patients treated with high-intensity multi-modal strategies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…81.7% of the tumors were AJCC stage II and it is also a high rate compared with previously published studies. 28,32,33 Our data on nodal involvement (15%) was the same as that for Chinese population 24 and low compared with previously reported data. 32,33 15% of the analyzed SCCTs recurred, this rate was higher to that reported in Chinese patients 24 and similar to the proportion found in the Mäkitie et al study.…”
Section: Tnm Classificationsupporting
confidence: 81%
See 3 more Smart Citations
“…81.7% of the tumors were AJCC stage II and it is also a high rate compared with previously published studies. 28,32,33 Our data on nodal involvement (15%) was the same as that for Chinese population 24 and low compared with previously reported data. 32,33 15% of the analyzed SCCTs recurred, this rate was higher to that reported in Chinese patients 24 and similar to the proportion found in the Mäkitie et al study.…”
Section: Tnm Classificationsupporting
confidence: 81%
“…As it was previously reported, 27,28,29,30,31 MTSCCs were more frequently found than BTSCC. Compared with previous reports, 27,28,29 this study revealed a lower proportion of BTSCCs, but other studies showed a similar BTSCC rate. 30,31 The mean age of 65.7 years detected in this study, was similar to previously reported data.…”
Section: Microscopic Differentiationsupporting
confidence: 68%
See 2 more Smart Citations
“…Jo et al 7 , reviewed 31 PSCCs of the upper aerodigestive tract and reported an identifiable high-risk HPV by in situ hybridisation in 68% of cases. The tumours related to HPV infection seem to have a better prognosis and for this reason, those authors propose reporting HPV status when these tumours are encountered 7 14 15 .…”
Section: Discussionmentioning
confidence: 99%